Branding of Fuel by Indian Petroleum Industry and its Impact (With Reference to the Branded Petrol) - Gupta, C.P.; Chaturvedi, Mitali (Indian Journal of Marketing, 2006)
India is becoming a global player. Government has and is deregulating various industrial sectors and is ending its monopoly. The liberalization process, which started in early 1990’s, has now placed India as a true global player in the global market. Name any industrial sector and the Indian people are ready to compete. Whether it is Information Technology or the Telecom sector, within a short span of time, the country has seen the emergence of an entirely new market category. A new area, which according to industry observers is setting trend in line with the global trends, is wherein petroleum companies are trying to build a loyal customer base by branding fuels. Generally fuels like petrol and diesel do not come under the category where there is much scope for product differentiation, and therefore branding of these products has been seen as a sea change in the Indian petroleum sector.